2011
DOI: 10.1112/jlms/jdq095
|View full text |Cite
|
Sign up to set email alerts
|

On sums of sets of primes with positive relative density

Abstract: In this paper we show that if A is a subset of the primes with positive relative density δ, then A + A must have positive upper density C1δefalse(normallogfalse(1/δfalse)false)2/3(log log(1/δ))1/3 in the natural numbers. Our argument uses the techniques developed by Green and Green‐Tao in their work on arithmetic progressions in the primes, in combination with a result on sums of subsets of the multiplicative subgroup of the integers modulo m.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 8 publications
2
20
0
Order By: Relevance
“…In [3] and [14] similar results as Theorem 1.3 appear with essentially same densities as in respective results for the primes. Proofs of those results in [3] and [14] proceed in different lines from ours.…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…In [3] and [14] similar results as Theorem 1.3 appear with essentially same densities as in respective results for the primes. Proofs of those results in [3] and [14] proceed in different lines from ours.…”
Section: Introductionsupporting
confidence: 70%
“…Indeed Ramaré and Ruzsa [14] had proved Theorem 1.1 with (1 − o(1)) replaced by (c − o(1)) for some constant c. Until recently the authors of [3] as well as the current author were unaware of that work. In light of [14], the achievement of Theorem 1.1 is getting the right constant.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Using 'W-trick', the strategy developed by Green-Tao, Chipeniuk and Hamel [5] showed that if A is a subset of the primes with positive relative lower density δ, then the set A + A has positive lower density at least…”
Section: Introductionmentioning
confidence: 99%